2021
DOI: 10.1088/1755-1315/749/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of a zero-fossil fuel distiller for bioethanol

Abstract: The study developed a Zero Fossil Fuel Distiller (ZFFD) to address environmental issues on bioethanol production from Nipa Sap. The Mariano Marcos State University had developed a distiller that can produce 95% fuel grade bioethanol powered by fuelwood. While burning woods provides a good heat source, this activity’s byproducts are not good for the environment. The scarcity of fuelwood will also be a problem for bulk production. Hence, the development of a ZFFD integrated with the Internet of Things (IoT) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…After the fermentation is done, the fermented Nipa Sap can be distilled. MMSU developed distillation systems that can produce up to 95% ethanol concentration using a fire wood [5] and full electric through renewable energy like solar [6]. In the latest development [6], the temperature was controlled but not the flowrate of the cooling system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the fermentation is done, the fermented Nipa Sap can be distilled. MMSU developed distillation systems that can produce up to 95% ethanol concentration using a fire wood [5] and full electric through renewable energy like solar [6]. In the latest development [6], the temperature was controlled but not the flowrate of the cooling system.…”
mentioning
confidence: 99%
“…The significance of this study will be applied to the larger capacity distillers [5] developed and produced by Mariano Marcos State University particularly those that are operated using a fixed flow rate cooling system and to the zero-fossil fuel distiller [6] that was not yet optimized. This study follows the process flowchart shown in Figure 1.…”
mentioning
confidence: 99%